The effects of power band performance technology on motorical abilities of young soccer players - Puzovic, V.; Djordjevic, D.; Djurovic, M.; Jakovljevic, V. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Athletes are constantly looking for the aids that would help them improve their performance. One of the most popular ergogenic aids is Power Band bracelet. Power Band contains thin polyester hologram, which is broadcasting the natural frequencies associated with the energy field of the human body. According to manufacturer`s assertion, it improves balance and muscle strength and flexibility of up to 30%. However, no scientific study confirms this claim. Thus the aim of our study was to investigate the influence of Powerband hologram on balance, flexibility, explosive strength and acceleration of young football players. Methods: Forty nine football players (age: 17.4±1.1) were subjected to: 1) one leg standing balance test, 2) sit and reach test, 3) squat and countermovement jump test and 4) sprint 10, 20 and 30m. Each subject performed each test 3 times: 1) without any bracelet, 2) with placebo bracelet and 3) with Powerband bracelet. Subjects were divided into 2 groups that differed in the order in which they placed bracelets (group A: 1) without bracelet, 2) with placebo bracelet, 3) with Power Band bracelet; group B: 1) without bracelet, 2) with Power Band bracelet, 3) with placebo bracelet) in order to test if warm up and habituation to the task affected results ahieved with bracelets. Results: When wearing both placebo and Power Band bracelet athletes performed better than when not wearing a bracelet in two tests: balance (no bracelet: 49.60±5.79 sec, with placebo bracelet: 60.04±6.37 sec, with Power Band bracelet: 66.60±5.99 sec) and flexibility (no bracelet: 9.95±1.12 cm, with placebo bracelet: 10.42±1.11 cm, with Powerband bracelet: 10.71±1.13 cm). Two way ANOVA repeated measures showed that wearing a bracelet was a factor that influenced results (Power Band vs no bracelet: P=0.002 and 0.021 for balance and flexibility retrospectively) and that observed differences in tests results were not dependent on the order in which athletes placed bracelets during performance of tests. Discussion: Contrary to the results of previously published studies (1-3), our study found that athletes performed significantly better in tests of balance and flexibility when wearing a bracelet. Those effects may be in part based on placebo effect, but the results of Two way ANOVA repeated measures suggests that there may also be the real effect of hologram on athletes energy field.